Eficácia do curativo de hidrogel com nanopartículas de prata na cicatrização de feridas crônicas: estudo clínico randomizado - Araújo, Juliano Gonçalves de (2017)
Chronic wounds pose a serious problem to public health in Brazil due to the large number of people affected, generating enormous public spending on treatment, as well as noticeably interfering in the quality of life of this population. The search for new, more effective and less onerous therapies has been challenging for the health institutions and professionals who treat these illnesses. Our aim is to evaluate the healing process in chronic wounds with topical use of experimental hydrogel dressings with silver nanoparticles (HNPAg), comparing them with dressings of calcium alginate with silver and silver polyurethane foam We invited 30 participants suffering from chronic wounds, who were randomized into 3 groups, each one receiving only one kind of treatment during 4 consecutive weeks. All wounds were photographed weekly using IMAGE! 1.51 software for digital measurement of the areas. Analysis of variance (ANOVA) was used, one- and two-way, in order to compare the averages between treatments and other variables, as well as Pearson correlation to verify if there was any connection between healing rate, treatment and number of weeks, using Bioestat 5.3 software with a significance level of 0.05. We verified that the HNPAg presented a higher final average healing rate (32.37%) compared to the alginate and foam (26.61 and 24.12%), respectively (p=0.0019); and a lower total treatment cost in the period analysed (RS179.00, R$3,967.00 and R$ 5,569.00), respectively (p<0.0001). Therefore, the HNPAg proved to be an effective, practical and cheap treatment, offering a viable option for use in public health institutions.